Mastering the Art of Oral Presentations - Stewart, John; Fulop, Dan (Ascent Audio, 2019)
Proven techniques to win over any audience and make any sale Mastering the Art of Oral Presentations is your expert guide to delivering memorable and effective speeches and presentations. Whether selling a product, offering a service, or bidding for a contract, your oral presentation skills can often determine success or failure. This invaluable resource delivers real-world advice and proven strategies to elevate your game and close the deal. Comprehensive coverage of preparation procedures, delivery techniques, and presentation strategies provide you with the tools and knowledge to motivate and persuade your audience. Emphasizing real-world versatility, this unique book delivers methods equally effective to both individual and team presentations. Drawing from decades of experience, authors John Parker Stewart and Don Fulop offer keen insight into the process of winning over an audience. From topics ranging from rhetorical devices and visual cues to body language and stage presence, this expert guide will help convey a take-home message that resonates and endures long after your presentation has concluded.
Online resource; Title from title page (viewed May 14, 2019)
Keywords: Language arts; Arts du langage; Audiobooks